Regulators of mitochondrial quality control differ in subcutaneous fat of metabolically healthy and unhealthy obese monkeys. Issue 4 (25th February 2017) - Kavanagh, Kylie; Davis, Ashley T.; Peters, Diane E.; LeGrand, Andre C.; Bharadwaj, Manish S.; Molina, Anthony J.A.
Abstract : Objective: Obesity exists with and without accompanying cardiometabolic disease, termed metabolically unhealthy obesity (MUO) and healthy obesity (MHO), respectively. Underlying differences in the ability of subcutaneous (SQ) fat to respond to nutrient excess are emerging as a key pathway. This study aimed to document the first spontaneous animal model of MHO and MUO and differences in SQ adipose tissue. Methods: Vervet monkeys ( Chlorocebus aethiops ; N  = 171) were screened for metabolic syndrome. A subset of MHO and MUO monkeys ( n  = 6/group) had SQ fat biopsies collected for histological evaluations and examination of key mitochondrial proteins. Results: Obesity was seen in 20% of monkeys, and within this population, 31% were healthy, which mirrors human prevalence estimates. MUO monkeys had more than 60% lower adiponectin concentrations despite similar fat cell size, uncoupling protein 3, and activated macrophage abundance. However, alternatively activated/anti‐inflammatory macrophages were 70% lower. Deficiencies of 50% or more in mitochondrial quality control regulators and selected mitochondrial fission and fusion markers were observed in the SQ fat of MUO monkeys despite comparable mitochondrial content. Conclusions: A novel and translatable spontaneously obese animal model of MHO and MUO, occurring independently of dietary factors, was characterized. Differences in mitochondrial quality and inflammatory cell populations of subcutaneous fat may underpin divergent metabolic health.